Post-trauma eventration.: Muscle disinsertion of the iliac crest. Based on one case observed. - Piacenza, Guillermo; Rocha, Osvaldo; Rodríguez, José Luis (Cirugía del Uruguay, 1984)
Description of a case of post-trauma eventration caused by muscular disinsertion, surgically repaired with the patient's own tissues and satisfactory evolu• tion.